La fabrique de la plastique du cheval au XVIIIe siècle : le modèle « antique » à l’épreuve de la leçon de dessin d’Edme Bouchardon (1748-1824) - Morwena Joly Parvex (In Situ)
The horse’s figure in the eighteenth century, the classical model challenged by Edme Bouchardon’s drawing lessons. During the eighteenth century, three mythical models (two of which are now lost) underpinned the notion of what the horse of a powerful ruler should look like : the equestrian statue of Marcus Aurelius at the Place du Capitole in Rome, the statue of the Duke of Sforza by Leonard da Vinci, and the classical écorché known as the Mattei Villa horse. Looking at these three models, all of them somewhat similar in appearance, it is easy to understand why it was difficult to bring about change in the way horses were depicted during the eighteenth century, even though many artistic debates surrounded this issue. The artist was little concerned by the question of movement, and it was veterinary surgeons who took up this problem. The ronde-bosse model offered to artists changed little before 1789. It was only during the Restoration period that new approaches began to emerge after the exhibition, at the 1817 Salon, of moulded plasters based on a dissected horse. These pieces, exhibited by the animal sculptor J.-N. Brunot, gave rise to a new treatise for artists on the horse’s anatomy, which remained a reference up to the beginning of the twentieth century.